Numerical Investigations of Injection Timing Effects on a GDI Engine Performance: Part B, In-Cylinder Emission Formation and Oxidation Process - Zhang, Yu; Yang, Ruomiao; Yan, Yuchao; Li, Ruijie; Fu, Jiahong; Liu, Zhentao (Frontiers in Energy Research, 2022)
The emphasis on environmental protection and energy security has promoted automobile engine technology towards low emission and economy. While the traditional port fuel injection (PFI) engine can hardly meet the last recommendation, the gasoline direct injection (GDI) engine becomes a hot research topic since its potential to reduce fuel consumption and emission. Since injection timing has a determining effect on overall engine performance this paper aimed to investigate the injection timing effects on mixture formation and emission. A 3D numerical simulation model of a 4-strokes GDI engine combustion chamber was adopted. In a previous work (Part A), the in-cylinder combustion process has been discussed. In this study, the simulation results demonstrate that with the injection timing advancing, the fuel-gas mixture was more uniform-distributed and combusted more completely; the NOx, UHC, soot had decreased sharply by 79.5%, 98.7%, 95.5%; the CO emission increased gradually by 14.7%. The optimized injection timing for this case was 300 CA BTDC. Moreover, this paper studied the in-cylinder views of injection timing effects on mixture formation and emission, providing reference to optimize injection of GDI engine.